Knowledge, perception and attitude of under-graduate and post-graduate medical students about antimicrobial use, resistance and stewardship at a tertiary care teaching hospital in rural Telangana, India - Chundru, Jayaram; D., Shailendra; Tirumalareddy, Rahul R.; Kumari, Harsha; Kovilakonda, Vishal P. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Inappropriate antimicrobial use contributes to antimicrobial resistance. Assessing knowledge, perception and attitude regarding antimicrobial use serves as a prelude to design and implement educational modules to promote rational antimicrobial use. Methods: An online questionnaire based cross-sectional study involving 338 medical students; under-graduates, interns and post-graduates was conducted in a medical college in south India. Chi-square test or Fisher exact test were used to determine association between variables. Results: Fifty percent of the participants (170/338) responded to the questionnaire. The responses were similar across undergraduates, interns and post-graduates. Majority of the responders had good knowledge regarding use of antimicrobials. Most of the participants (92.35%) expressed that a broad-spectrum antimicrobial should be started to treat a serious infection while awaiting culture and sensitivity reports and 88.82% did not prefer to use antimicrobial agents for common cold. Similarly, most of the respondents (93.56%) were aware of the fact that antimicrobial resistance is a global problem. However, many of them (74.71%) were not aware of antimicrobial stewardship programme in their college. Conclusions: This study revealed that most of the students had good knowledge, fair perception and positive attitude regarding the use of, and resistance to antimicrobial agents but not about stewardship programmes. Proactive measures are required to sensitise medical students on antimicrobial stewardship programmes.